2015
DOI: 10.1016/j.rgmxen.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal factors associated with the development of cow's milk protein allergy

Abstract: The prevalence of cow's milk protein allergy (CMPA) has increased in recent years, and is associated with antimicrobial use during the perinatal period, prematurity, the type of childbirth, and the decrease in breastfeeding. The aim of this study was to analyze whether there is any association between these factors and the development of CMPA. Material and methods: A retrospective, comparative, cross-sectional, observational study was conducted by reviewing the case records of 101 children diagnosed with CMPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Toro et al (22) observed a statistically significant association between CMA and the use of antibiotics in the last trimester of pregnancy and the duration of breastfeeding, but not with gestational age and type of delivery. Tsaubori et al (23) , on the other hand, in a review article report that patients delivered by cesarean section, use of parenteral nutrition and the hospitalization of preterm newborns play a key role in developing altered microbiota (dysbiosis), which can be risk factors for CMA.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Toro et al (22) observed a statistically significant association between CMA and the use of antibiotics in the last trimester of pregnancy and the duration of breastfeeding, but not with gestational age and type of delivery. Tsaubori et al (23) , on the other hand, in a review article report that patients delivered by cesarean section, use of parenteral nutrition and the hospitalization of preterm newborns play a key role in developing altered microbiota (dysbiosis), which can be risk factors for CMA.…”
Section: Discussionmentioning
confidence: 98%
“…According to the literature, about half of cases of FPIPC in infants occur during exclusive breastfeeding (1) . However, the studies published on rectal bleeding in neonates (20)(21)(22) do not include samples with most preterm infants, as described in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations